The Seventh International Conference on Vibration Problems ICOVP 2005 05-09 September 2005, Istanbul, Turkey - Inan, Esin; Kiris, Ahmet (Springer Proceedings in Physics,, 2007)
This volume presents the Proceedings of the Seventh International Conference on Vibration Problems, held in Istanbul, Turkey, 05-09 September 2005. As with the earlier conferences in the ICOVP series, the purpose of ICOVP-2005 was to bring together scientists with different backgrounds, actively working on vibration-related problems of engineering both in theoretical and applied fields. The main objective did not lie, however, in reporting specific results as such, but rather in joining/exchanging different languages, questions and methods developed in the respective disciplines, and to thus stimulate a broad interdisciplinary research. The topics, indeed, vary from the effect of ground motion on the stochastic response of suspension bridges to coupling effects between different vibrations in rotor-blade systems. All lectures delivered at the Conference are recorded in their full text. Audience: Scientists, researchers and graduate students in physics and engineering.